2018
DOI: 10.1136/bmjopen-2018-021623
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anemia and underweight as determinants of pregnancy outcomes: cohort study in eastern rural Maharashtra, India

Abstract: ObjectivesTo study the trend in the prevalence of anaemia and low BMI among pregnant women from Eastern Maharashtra and evaluate if low BMI and anaemia affect pregnancy outcomes.DesignProspective observational cohort study.SettingCatchment areas of 20 rural primary health centres in four eastern districts of Maharashtra State, India.Participants72 750 women from the Nagpur site of Maternal and Newborn Health Registry of NIH’s Global Network, enrolled from 2009 to 2016.Main outcome measuresMode of delivery, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 41 publications
11
104
1
9
Order By: Relevance
“…This finding is supported by several studies, [27][28][29][30] which have highlighted that >50% of pregnant women in India are anaemic. This finding is supported by several studies, [27][28][29][30] which have highlighted that >50% of pregnant women in India are anaemic.…”
Section: Interpretation In Light Of Evidencesupporting
confidence: 67%
See 1 more Smart Citation
“…This finding is supported by several studies, [27][28][29][30] which have highlighted that >50% of pregnant women in India are anaemic. This finding is supported by several studies, [27][28][29][30] which have highlighted that >50% of pregnant women in India are anaemic.…”
Section: Interpretation In Light Of Evidencesupporting
confidence: 67%
“…Anaemia was identified as the most common and important high-risk condition affecting pregnant women at both study sites. This finding is supported by several studies, [27][28][29][30] which have highlighted that >50% of pregnant women in India are anaemic. 31 The Government of India has recognised the importance of the early recognition and treatment of anaemia throughout a woman's life-course and have recently launched the 'Anemia Mukt Bharat' (Anaemia Free India) campaign.…”
Section: Interpretation In Light Of Evidencesupporting
confidence: 67%
“…We did not observe a significant association for girls, but it’s not clear why such association can differ among boys and girls. Younger mothers tend to be undernourished and develop anemia during pregnancy – which could be the possible mechanisms for this association [1618]. We also observed significant adverse effects of maternal undernutrition on low birth weight, independent of socioeconomic status.…”
Section: Discussionmentioning
confidence: 66%
“…were secondary clusters. The primary clusters' spatial window was located in the North West Amhara and Northeast part of BenishangulGumuz, which was centered at 11.57418N, 36.498123 E with 122.56km radius, and Log-Likelihood ratio (LLR) of 11.82, at p < 0.01. It showed that women within the spatial window had 2.66 times higher risk of LBW as compared to women outside the window.…”
Section: Spatial Scan Statistics Of Low Birth Weight In Ethiopiamentioning
confidence: 99%